Critical Appraisal of Lakshanaskandha of Bruhat-Tryaee with special reference to Pandu - Rajput Rajendrasinh; Darshna Pandya; Karan Surati (International Journal of Ayurveda and Pharma Research, 2025)
Lakshanas (symptoms and signs) are the backbone of clinical practice, whether in the form of physiological or pathological condition, in context of diagnosis or treatment one need to rely on the manifested symptoms only. Here it is very much important to understand pathophysiology of Pandu in different given context to understand seriousness of the condition and to plan the treatment accordingly. Materials and Methods: Mainly Bruhattrayee i.e., Charaka Sahmita, Sushruta Sahmita and Ashtanga Hridaya with its well-known commentary was selected as main text and Pandu has been searched. Results: It appears 23 times in Charaka Samhita, 21 times in Sushruta Samhita, and 8 times in Ashtanga Hrudaya. In the context of clinical signs and symptoms, references to Pandu were identified as follows: 2 instances as Purvarupa, 12 as Rupa, 7 as Upadrava, 2 as Ariṣhṭa, and 29 instances categorized under miscellaneous references. Discussion: The therapeutic approach to Pandu Roga must be individualized and rooted in a comprehensive understanding of its Samprapti. The selection of treatment modalities should be based on the underlying aetiology. Conclusion: Each symptom has its own specific Samprapti. Different symptoms can arise from various mechanisms. To effectively address Pandu, it is crucial to evaluate the causative factors and pathogenesis and plan the treatment accordingly.